Study of Diverse Leg Geometry Effect on the Performance of Segmented Thermoelectric Generator with the Same Leg Volume - Khalil, Alkhadher; Elhassnaoui, Ahmed; Yadir, Said; Abdellatif, Obbadi; Errami, Youssef; Sahnoun, Smail (Trends in Sciences, 2023)
When developing any product, one of the factors that determine its price is the volume of the product. In this paper, the effect of various geometrical forms on the performance of a segmented TEGs with the same leg volume was performed. For this purpose, a numerical study was performed using the finite element method (FEM) for different geometrical shapes by considering 3 following forms: Rectangular-leg, Pin-leg, and Cone-leg. In each region, Bismuth Telluride was deposited on the cold side while Lead Telluride was placed on the hot side. Two cases were studied. In the 1st case, the 2 regions’ the same length, for n and p types, which constitute the leg was taken. While in the 2nd case, all forms of the same volume were evaluated by taking a variable leg length and a fixed cross-sectional area of the hot side. The optimal ratios of the Bismuth Telluride lengths in and regions for the Rect-leg, Pin-leg, and Cone-leg were studied. The obtained results showed that the Rectangular-leg model in the 1st case presents the highest output power and efficiency with about 0.3019 watt and 12.47 % with leg length values of ( and ) 1 and 4.5 mm, respectively. Based on the simulation results, we conclude that the leg form and the length ratio influence the performance of the segmented TEGs. The findings indicate that the Rect-leg model presents the best performance. HIGHLIGHTS Difference of the internal temperature distribution with the variable leg geometry The effect of the segmented thermoelectric leg length ratios on internal resistance and thermal conductance In the segmented TEGs Efficiency decreases with increasing the length ratio of materials in lower temperature range Increasing the performance in the segmented TEGs compared to the traditional TEG GRAPHICAL ABSTRACT